Resurrection of Astragalus gorganicus Sirj. & Rech.f. (Fabaceae) - Bagheri, Ali; Maassoumi, Ali Asghar; Osaloo, Shahrokh Kazempour (Phytotaxa, 2025)
Astragalus gorganicus Sirj. & Rech.f., originally described from the Alborz Mountains of northern Iran, has long been treated as a synonym of A. lineatus. A critical reassessment of its type material together with additional herbarium specimens supports its recognition as a distinct species. Morphologically, A. gorganicus is distinguished by the presence of inflated legumes, in contrast to the inflated calyces that characterize A. lineatus and sect. Grammocalyx. Three subsequently described taxa, A. coelicolor, A. nezva-montis, and A. plagiophacos, are here regarded as conspecific with A. gorganicus and reduced to its synonymy. In addition, sect. Plagiophaca, formerly separated from sect. Malacothrix on the basis of fruit morphology, is synonymized with sect. Malacothrix owing to overlapping diagnostic traits. An emended species description is provided, highlighting the systematic importance of mature fruit morphology for species delimitation in this morphologically complex group.